2020
DOI: 10.1126/sciadv.abb8235
|View full text |Cite
|
Sign up to set email alerts
|

Are small farms more performant than larger ones in developing countries?

Abstract: Meta-regressions of around 1000 cases published over the period 1997–2018 suggest that the direction of the relationship between land area and agricultural performance strongly depends on the performance indicator selected. Net value and efficiency indicators show that larger farms tend to be more performant than smallholders, while the simpler but ubiquitous gross output indicators support an inverse relationship (IR). In addition, this study also indicates a decreasing record of IR in the literature over tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 90 publications
1
12
0
Order By: Relevance
“…Based on the above data, we use the maxDEA8 Basic software to calculate the production efficiency values of 135 seed-producing corn farmers in Zhangye City. Previous studies have shown that the scale of farmers' planting has a certain impact on production efficiency [52][53][54][55][56]. In order to explore the impact of the corn planting scale of farmers on their agricultural production efficiency, we draw a graph of the relationship between farmer's production efficiency and planting scale.…”
Section: Farmers' Production Efficiency According To the Dea Methodsmentioning
confidence: 99%
“…Based on the above data, we use the maxDEA8 Basic software to calculate the production efficiency values of 135 seed-producing corn farmers in Zhangye City. Previous studies have shown that the scale of farmers' planting has a certain impact on production efficiency [52][53][54][55][56]. In order to explore the impact of the corn planting scale of farmers on their agricultural production efficiency, we draw a graph of the relationship between farmer's production efficiency and planting scale.…”
Section: Farmers' Production Efficiency According To the Dea Methodsmentioning
confidence: 99%
“…Some studies used renting-in land and double cropping as instruments to estimate the farm size and productivity relationship (Lamb, 2003). However, several studies do not use an instrumental strategy despite acknowledging the presence of endogeneity (see for example, (Omotilewa et al, 2021;Garzón Delvaux et al, 2020). We too rely on the OLS results due to lack of a relevant exogenous instrument.…”
Section: Potential Endogeneitymentioning
confidence: 99%
“…The choice of the output variables (net returns, gross revenue, yield, total factor productivity, etc.) is used in the analysis (Garzon Delvaux et al, 2020). For instance, Rada and Fuglie (2019) have found, based on a set of case studies, that the size-productivity relationship evolves with the level of economic development of the country.…”
Section: Literature Reviewmentioning
confidence: 99%